Preparation method of high-crystallinity bamboo powder fiber tableware
Patent Information
- Application Number
- CN202611010415.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-08
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2046-07-08
AI Technical Summary
[0003]本发明的目的在于提供高结晶度竹粉纤维餐具的制备方法,以解决现有技术中天然竹粉自身结晶度低、与树脂基体界面相容性差导致复合制品性能受限的技术问题
1、本发明通过将蒸汽爆破与水热处理相结合,并采用程序控温系统进行梯度冷却,有效促进了竹粉中纤维素分子链的重新排列与规整;缓慢的降温过程有利于晶体的完善和生长,从而提高了竹粉纤维的结晶度和热稳定性,增强了餐具的结构强度;
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of bio-based composite materials, specifically a method for preparing highly crystalline bamboo powder fiber tableware. Background Technology
[0002] Bamboo fiber is often blended with resins such as polylactic acid (PLA) to manufacture composite tableware. However, using natural bamboo powder directly as a filler in composite materials has the following drawbacks: its dense lignocellulose structure contains amorphous regions, which restricts molecular chain rearrangement and results in low crystallinity; moreover, untreated bamboo powder has poor interfacial compatibility with the resin matrix and lacks heterogeneous nucleation sites, which limits the flexural modulus and heat distortion temperature of the final product. To improve these defects, existing technologies often modify bamboo powder, mainly through physical reconstruction and in-situ grafting. Physical reconstruction utilizes steam explosion and subcritical hydrothermal annealing to promote the recombination of cellulose hydrogen bond networks and improve crystallinity; in-situ grafting introduces coupling agents and nucleating agents on the fiber surface to improve the interfacial bonding force with the resin matrix. Currently, the common method for preparing such composite tableware is to melt-blend modified bamboo powder with resin and then injection mold it. Summary of the Invention
[0003] The purpose of this invention is to provide a method for preparing highly crystalline bamboo powder fiber tableware, thereby solving the technical problem in the prior art where the low crystallinity of natural bamboo powder and poor interfacial compatibility with the resin matrix limit the performance of composite products. Specifically, the technical solution of this invention includes the following steps: A. Take bamboo powder, pretreat the bamboo powder by impregnation with a sodium bicarbonate solution with a mass concentration of 0.5-1.0wt%, and then adjust the moisture content to 10-15wt% by dehydration and drying to obtain pretreated bamboo powder. B. Place the pretreated bamboo powder in a steam explosion tank, introduce saturated steam to raise the temperature to 160-180℃, maintain the pressure for 30-45 minutes, then release the pressure and wash with water until neutral to obtain explosion bamboo powder. C. Disperse the blasted bamboo powder in an aqueous medium to prepare an aqueous suspension, heat it in a sealed container to 140-160℃ and keep it at a constant temperature for 2-4 hours; D. After the isothermal treatment, the mixture is gradually cooled at a cooling rate of 1.0-2.5℃ / min. When the temperature drops to 95-100℃, a composite dispersion prepared by mixing silane coupling agent, amide nucleating agent and water dispersion medium is added and stirred for 30-40 minutes. The mixture is then cooled to room temperature at a cooling rate of 1.0-2.5℃ / min, followed by solid-liquid separation and drying, or direct drying, to obtain modified bamboo powder fiber. E. Take 20-40 parts by weight of modified bamboo powder fiber and 60-80 parts by weight of polylactic acid or polybutylene succinate matrix resin, and then perform melt blending and injection molding.
[0004] Preferably, the bamboo powder in step A is natural bamboo powder that has been sieved through an 80-mesh sieve.
[0005] Preferably, in step D, the composite dispersion is prepared by ultrasonic dispersion and has a solid content of 1.5-3.0 wt%; the amount of silane coupling agent added is 0.3-0.8 wt% of the mass of the blasted bamboo powder, and the amount of amide nucleating agent added is 1.0-2.0 wt% of the mass of the blasted bamboo powder; in step E, when the matrix resin is polylactic acid, the processing temperature is 155-180℃; when the matrix resin is polybutylene succinate, the processing temperature is 130-160℃.
[0006] Preferably, in the composite dispersion of step D, the amount of silane coupling agent added is 0.5-0.6 wt% of the mass of the blasted bamboo powder, and the amount of amide nucleating agent added is 1.2-1.6 wt% of the mass of the blasted bamboo powder.
[0007] Preferably, the silane coupling agent in step D is 3-aminopropyltriethoxysilane, and the amide nucleating agent is N,N'-ethylenebisstearamide.
[0008] Preferably, the cooling rate in step D, which continues to cool to room temperature, is 1.0 °C / min.
[0009] Preferably, the drying process in step D is spray drying or freeze drying after filtration. When the drying process is spray drying, the inlet air temperature is 85-150°C and the outlet air temperature is 42-90°C.
[0010] Preferably, in step E, the modified bamboo powder fiber is 30 parts by mass and the matrix resin is 70 parts by mass.
[0011] Preferably, in step A, the impregnation is carried out at a liquid-solid mass ratio of 3:1-5:1, the impregnation pretreatment temperature is 20-30℃, and the time is 1-2 hours; in step B, the pressure is released in less than 0.1s; in step C, the solid content of the aqueous suspension is 10-20wt%, and the stirring rate is 100-300rpm.
[0012] This invention provides an improved method for preparing highly crystalline bamboo fiber tableware, which, compared with the prior art, has the following improvements and advantages: 1. This invention combines steam explosion with hydrothermal treatment and uses a programmed temperature control system for gradient cooling, which effectively promotes the rearrangement and regularization of cellulose molecular chains in bamboo powder; the slow cooling process is conducive to the perfection and growth of crystals, thereby improving the crystallinity and thermal stability of bamboo powder fibers and enhancing the structural strength of tableware. 2. In a specific cooling stage, the present invention introduces a composite dispersion composed of silane coupling agent and amide nucleating agent to modify the surface of bamboo powder. The silane coupling agent effectively improves the interfacial compatibility between bamboo powder fiber and matrix resins such as polylactic acid or polybutylene succinate, while the amide nucleating agent promotes the crystallization of the matrix resin. The two work together to improve the processing and molding effect of the composite material and the comprehensive mechanical properties of the final tableware. Detailed Implementation
[0013] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to specific embodiments.
[0014] Example 1
[0015] This embodiment provides a method for preparing highly crystalline bamboo powder fiber tableware, which specifically includes the following steps: S1 Bamboo Powder Pretreatment: Take natural bamboo powder that has been sieved through an 80-mesh sieve, add sodium bicarbonate solution with a mass concentration of 0.5wt% at a liquid-to-solid mass ratio of 4:1, and soak at 25℃ for 1.5 hours; after soaking, adjust the moisture content of the bamboo powder to 12wt% to obtain pretreated bamboo powder. S2 Steam Explosion Treatment: Pretreated bamboo powder is placed in a steam explosion tank, saturated steam is introduced, and the temperature inside the tank is raised to 170°C. The pressure is maintained at the corresponding saturated steam pressure for 40 minutes, and the pressure is released within less than 0.1 seconds. The explosive material is collected and washed with deionized water until neutral to obtain exploded bamboo powder. S3 Subcritical Hydrothermal Annealing: Exploded bamboo powder is dispersed in an aqueous medium to prepare an aqueous suspension with a solid content of 15wt%; the aqueous suspension is transferred into a high-pressure reactor and heated to 150℃ under a stirring condition of 200rpm in a closed environment, and kept at a constant temperature for 3 hours to obtain the hydrothermal annealing solution. S4 Program Cooling and In-situ Grafting Modification: After the isothermal treatment, gradient cooling is performed at a cooling rate of 2.0℃ / min; when the temperature of the reaction system drops to 95℃, the pre-ultrasonically dispersed composite dispersion is pumped into the high-pressure reactor and kept at the temperature and stirred for 35 minutes; then the temperature is further cooled to room temperature at a cooling rate of 1.0℃ / min to obtain the grafted modified slurry. This process introduces heterogeneous nucleation sites on the fiber surface through in-situ grafting, thereby improving the interfacial compatibility with the resin matrix. The composite dispersion is prepared by ultrasonic dispersion of a mixture of silane coupling agent, amide nucleating agent, surfactant, and aqueous dispersion medium. The surfactant can be Tween-80 or sodium dodecyl sulfate, added at 0.5wt%-1.5wt% of the aqueous dispersion medium. The silane coupling agent is 3-aminopropyltriethoxysilane, added at 0.5wt% of the mass of the blasted bamboo powder. The amide nucleating agent is N,N'-ethylenebis-stearamide, added at 1.5wt% of the mass of the blasted bamboo powder. The amount of aqueous dispersion medium added is controlled to achieve a solid content of 2wt% in the composite dispersion. The ultrasonic dispersion conditions are: ultrasonic power of 400W and ultrasonic time of 20 minutes. S5 Solid-liquid separation and drying: The grafted modified slurry obtained in step S4 is filtered and then freeze-dried. The freezing temperature is set to -45℃ and the vacuum degree is set to 15Pa to obtain modified bamboo powder fiber. Freeze-drying can effectively maintain the three-dimensional structure of the fiber and avoid agglomeration. When the freezing temperature is higher than -45℃ or the vacuum degree is higher than 15Pa, the water sublimation will be incomplete, the fibers will agglomerate, and the mechanical properties of the composite material will decrease. If the freezing temperature is lower than -45℃ or the vacuum degree is lower than 15Pa, the process efficiency will be reduced and there will be no further improvement to the fiber structure. Preparation of S6 composite tableware: By mass, 30 parts of modified bamboo powder fiber and 70 parts of polylactic acid were mixed and melt-blended at a processing temperature of 155-180℃, followed by injection molding to obtain bamboo powder fiber tableware; melt blending was carried out in a twin-screw extruder at a processing temperature of 165℃ and a screw speed of 150 rpm; injection molding was carried out in an injection molding machine at an injection temperature of 175℃ and an injection pressure of 70 MPa; When the processing temperature is below the lower limit of the above-mentioned set range, the melt fluidity of polylactic acid decreases, resulting in a decrease in the flexural modulus of the tableware; when the processing temperature is above the upper limit of the above-mentioned set range, polylactic acid undergoes thermal degradation; in this embodiment, the processing temperature is 165°C, which maintains the melt fluidity and avoids thermal degradation.
[0016] Example 2
[0017] The preparation steps in this embodiment are basically the same as those in Example 1, except that the process parameters are adjusted as follows: In S1, the liquid-to-solid mass ratio is adjusted to 3:1, the sodium bicarbonate solution concentration is adjusted to 1.0 wt%, the impregnation temperature is 20℃, the impregnation time is 1 hour, and the bamboo powder moisture content is adjusted to 10 wt%. In S2, the steam explosion temperature is 160℃ and the pressure holding time is 30 minutes; In S3, the water suspension has a solid content of 10 wt%, the stirring rate is 100 rpm, and it is heated to 140°C in a closed environment and kept at a constant temperature for 2 hours to obtain a hydrothermal annealing solution. This solution plasticizes the amorphous region of cellulose. In S4, the cooling rate is 2.5℃ / min. When the temperature drops to 100℃, the composite dispersion is pumped in, kept warm and stirred for 30 minutes, and then cooled to room temperature at 2.5℃ / min to obtain the grafted modified slurry, thereby forming a uniform nucleation layer on the fiber surface. In the composite dispersion, the amount of 3-aminopropyltriethoxysilane added is 0.3wt% of the mass of the bursting bamboo powder, and the amount of N,N'-ethylene bis-stearamide added is 1.0wt% of the mass of the bursting bamboo powder. The amount of water dispersion medium added is controlled to make the solid content of the composite dispersion 1.5wt%. The ultrasonic dispersion conditions are: ultrasonic power of 300W and ultrasonic time of 15 minutes. In step S5, the grafted and modified slurry obtained in step S4 is directly subjected to low-temperature spray drying. The inlet air temperature is set to 120-150℃ and the outlet air temperature is set to 70-90℃. In this embodiment, the inlet air temperature is 130℃ and the outlet air temperature is 75℃, resulting in modified bamboo powder fiber. This drying method can quickly remove moisture and obtain fiber powder with good dispersibility. If the inlet air temperature is higher than 150℃, the silane coupling agent grafted on the fiber surface is prone to partial thermal decomposition, reducing interfacial compatibility. If the inlet air temperature is lower than 80℃, the drying efficiency is low, the powder moisture content is high, and the blending effect is affected. In step S6, 20 parts by weight of modified bamboo fiber and 80 parts by weight of polylactic acid are mixed, melt-blended, and injection molded to obtain tableware products. The melt blending is carried out in a twin-screw extruder, with a processing temperature set at 165-175℃, specifically 170℃ in this embodiment, and a screw speed of 120 rpm. The injection molding temperature is 170℃, and the injection pressure is 60 MPa. A processing temperature of 170℃ ensures that the modified bamboo fiber and resin are fully and uniformly mixed. If the processing temperature is lower than 165℃, uneven blending will occur. If the processing temperature is higher than 175℃, partial degradation of the resin will occur. When the processing temperature is 165℃ or 175℃, the blending can still be effectively completed and the flexural modulus requirements of the product can be met.
[0018] Example 3
[0019] The preparation steps in this embodiment are basically the same as those in Example 1, except that the process parameters are adjusted as follows: In S1, the liquid-to-solid mass ratio is 5:1, the sodium bicarbonate solution mass concentration is 0.8wt%, the impregnation temperature is 30℃, the impregnation time is 2 hours, and the bamboo powder moisture content is adjusted to 15wt%. In S2, the steam explosion temperature is 180℃ and the pressure holding time is 45 minutes; In S3, the water suspension has a solid content of 20wt%, the stirring rate is 300rpm, and it is heated to 160℃ in a closed system and kept at a constant temperature for 4 hours to obtain a hydrothermal annealing solution. This process further promotes the recombination of cellulose hydrogen bond network. In S4, the cooling rate is 1.5℃ / min. When the temperature drops to 95℃, the composite dispersion is pumped in, kept warm and stirred for 40 minutes, and then cooled to room temperature at 1.5℃ / min to obtain the grafted modified slurry, thereby effectively improving the interfacial compatibility. In the composite dispersion, the amount of 3-aminopropyltriethoxysilane added is 0.8wt% of the mass of the bursting bamboo powder, and the amount of N,N'-ethylene bis-stearamide added is 2.0wt% of the mass of the bursting bamboo powder. The amount of water dispersion medium added is controlled to make the solid content of the composite dispersion 3.0wt%. The ultrasonic dispersion conditions are: ultrasonic power of 500W and ultrasonic time of 30 minutes. In step S5, the grafted and modified slurry obtained in step S4 is filtered and then freeze-dried to obtain modified bamboo powder fiber. The freezing temperature is set to -45℃ and the vacuum degree is set to 15Pa to ensure that the fiber maintains a good pore structure during the drying process. If the freezing temperature and vacuum degree exceed the set range, when the freezing temperature is higher than the upper limit of the set range, the fiber structure will collapse, reducing the specific surface area and subsequent modification effect. In step S6, 40 parts by weight of modified bamboo fiber and 60 parts by weight of polylactic acid are mixed, melt-blended, and injection molded to obtain tableware products. The melt blending is carried out in a twin-screw extruder, with the processing temperature set at 170-180℃, specifically 175℃ in this embodiment, and the screw speed at 180 rpm. The injection molding temperature is 180℃, and the injection pressure is 80 MPa. Specifically, the melt state is optimal at 175℃. At a processing temperature of 170℃, the melt viscosity increases, and at a processing temperature higher than 180℃, thermal degradation occurs, thus affecting the heat distortion temperature of the tableware.
[0020] Example 4
[0021] The preparation steps in this embodiment are basically the same as those in Example 1, except that the process parameters are adjusted as follows: In S1, the liquid-to-solid mass ratio is 4:1, the sodium bicarbonate solution mass concentration is 0.7wt%, the impregnation temperature is 25℃, the impregnation time is 1.5 hours, and the bamboo powder moisture content is adjusted to 13wt%. In S2, the steam explosion temperature is 175℃ and the pressure holding time is 35 minutes; In S3, the water suspension has a solid content of 15wt%, the stirring rate is 200rpm, and it is heated to 155℃ in a sealed environment and kept at a constant temperature for 3 hours. In S4, the programmed cooling rate is 2.0℃ / min. When the temperature drops to 98℃, the composite dispersion is pumped in, kept warm and stirred for 35 minutes, and then cooled to room temperature at a rate of 1.0℃ / min. In the composite dispersion, the amount of 3-aminopropyltriethoxysilane added is 0.6wt% of the mass of the bursting bamboo powder, and the amount of N,N'-ethylene bis-stearamide added is 1.3wt% of the mass of the bursting bamboo powder. In S5, low-temperature spray drying is used, with the inlet air temperature set at 85℃ and the outlet air temperature set at 42℃. In S6, 30 parts by weight of modified bamboo fiber and 70 parts by weight of polybutylene succinate are mixed and melt-blended in a twin-screw extruder at a processing temperature of 155°C and a screw speed of 130 rpm. Then, the mixture is injection molded in an injection molding machine at a temperature of 160°C and an injection pressure of 65 MPa to obtain tableware products.
[0022] Comparative Example 1: The difference between this comparative example and Example 1 is that the sodium bicarbonate impregnation pretreatment in step S1 is omitted, and the natural bamboo powder is directly adjusted to a moisture content of 12wt% before proceeding to step S2. Other operating steps and process parameters are exactly the same as in Example 1.
[0023] Comparative Example 2: The difference between this comparative example and Example 1 is that the steam explosion treatment in step S2 is omitted, the pretreated bamboo powder is not exploded, and the water suspension is directly prepared for step S3. Other operating steps and process parameters are exactly the same as those in Example 1.
[0024] Comparative Example 3: The difference between this comparative example and Example 1 is that the subcritical hydrothermal annealing temperature in step S3 is replaced by 180°C instead of 150°C, and the dry heat treatment is maintained for 3 hours. The water medium suspension treatment is not used. Other operating steps and process parameters are exactly the same as in Example 1.
[0025] Comparative Example 4: The difference between this comparative example and Example 1 is that the gradient cooling procedure in step S4 is omitted, and the reaction system is naturally cooled to room temperature after step S3. Other operating steps and process parameters are exactly the same as in Example 1.
[0026] Comparative Example 5: The difference between this comparative example and Example 1 is that the operation of pumping in the composite dispersion when the temperature drops to 95°C in step S4 is omitted, and the in-situ grafting modification of silane coupling agent and amide nucleating agent is not performed. Other operation steps and process parameters are exactly the same as in Example 1.
[0027] Comparative Example 6: The difference between this comparative example and Example 1 is that the modified bamboo powder fiber in step S6 is replaced with blasted bamboo powder that has not been treated in step S4, while the other operating steps and process parameters are exactly the same as in Example 1.
[0028] Performance testing and data sheets: According to GB / T, the crystallinity index of bamboo powder fiber was tested by X-ray diffraction, the crystallinity of the composite matrix was tested by differential scanning calorimetry, the flexural modulus was tested according to GB / T9341 standard, and the heat distortion temperature was tested according to GB / T1634 standard. The mechanical properties and heat resistance of tableware products were evaluated in this way; the test methods of each group of samples were consistent. Sample data are shown in Table 1: Table 1 Performance test results of each group of samples
[0029] As can be seen from the comparison of the test results of Example 1 and Comparative Example 1 in Table 1, after omitting the sodium bicarbonate impregnation pretreatment, the crystallinity index of bamboo powder fiber, the crystallinity of the composite matrix, the flexural modulus and the heat distortion temperature all decreased; during the steam explosion process, hemicellulose deacetylation generates organic acids. Without the neutralization of weak base, cellulose is more prone to autocatalytic hydrolysis, resulting in a decrease in molecular chain length. The effective chain segments that can be rearranged in the subsequent hydrothermal annealing stage are reduced, the degree of crystallization of bamboo powder fiber decreases, and the reinforcing skeleton effect is weakened; The comparison of the test results of Example 1 and Comparative Example 2 in the table shows that all performance indicators decreased after the steam explosion treatment was omitted. Steam explosion can loosen the cell wall structure of bamboo powder and remove some amorphous hemicellulose, exposing more active hydroxyl groups of cellulose. Without this step, the dense lignocellulose structure is still retained, subcritical water cannot fully enter the amorphous region, the degree of cellulose chain rearrangement is limited, and the surface reaction sites for subsequent in-situ grafting are reduced. Therefore, the crystallinity of bamboo powder fiber and the ability of composite interface to induce crystallization both decrease. The comparison of the test results of Example 1 and Comparative Example 3 in the table shows that after replacing subcritical hydrothermal annealing with high-temperature dry heat treatment, the crystallinity index of bamboo powder fiber and the performance of composite products both decreased more significantly. Under high temperature and high pressure, water medium can plasticize the amorphous region of cellulose and promote the reorganization of hydrogen bond network. Under dry heat conditions, the lack of this polar medium results in insufficient molecular chain mobility, making it difficult to complete effective rearrangement. At the same time, the higher temperature will also cause thermal degradation of cellulose, which will reduce the strength of the reinforcing phase skeleton. Therefore, the flexural modulus and heat distortion temperature are significantly reduced.
[0030] The comparison of the test results of Example 1 and Comparative Example 4 in the table shows that after omitting the gradient cooling program, the crystallinity index of bamboo powder fiber, the crystallinity of the composite matrix and the heat resistance of the product all decreased. The programmed cooling provides a continuous time condition for the cellulose chain segments to further enter the lattice. During the natural cooling process, the cooling rate is uncontrollable, some non-equilibrium conformations are retained, the degree of lattice perfection is insufficient, and the internal stress is high. Therefore, the rigidity of the fiber itself and the dimensional stability of the composite material are both affected. A comparison of the test results of Example 1 and Comparative Example 5 in the table shows that, after omitting the in-situ grafting modification of the composite dispersion, the crystallinity index of bamboo powder fiber did not change significantly, but the crystallinity of the composite matrix, flexural modulus, and heat distortion temperature decreased significantly. Subcritical hydrothermal annealing and programmed cooling can still improve the crystallinity of cellulose itself, so the crystallinity of bamboo powder fiber remains at a high level. However, without silane coupling agents and amide nucleating agents, the heterogeneous nucleation sites on the fiber surface decreased, the interfacial compatibility with the resin matrix decreased, and the matrix resin was difficult to form a high crystalline structure during the molding and cooling process, so the thermal and mechanical properties decreased more significantly. Comparing the test results of Example 1 and Comparative Example 6 in the table, it can be seen that after replacing the modified bamboo powder fiber with blasted bamboo powder that has not been grafted in situ, the crystallinity, flexural modulus and heat distortion temperature of the composite matrix all decreased. Although blasted bamboo powder has certain loose structural characteristics, its cellulose crystal perfection and surface nucleation layer are insufficient when it is not treated with hydrothermal annealing and surface grafting. When added to the resin as a filler, its crystallization induction effect on the matrix is limited and the interfacial bonding strength is low. Therefore, it is difficult to obtain the comprehensive performance shown in Example 1.
[0031] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the technical solutions of the present invention.
Claims
1. A method for preparing highly crystalline bamboo powder fiber tableware, characterized in that, Includes the following steps: A. Take bamboo powder, pretreat the bamboo powder by impregnation with a sodium bicarbonate solution with a mass concentration of 0.5-1.0wt%, and then adjust the moisture content to 10-15wt% by dehydration and drying to obtain pretreated bamboo powder. B. Place the pretreated bamboo powder in a steam explosion tank, introduce saturated steam to raise the temperature to 160-180℃, maintain the pressure for 30-45 minutes, then release the pressure and wash with water until neutral to obtain explosion bamboo powder. C. Disperse the blasted bamboo powder in an aqueous medium to prepare an aqueous suspension, heat it in a sealed container to 140-160℃ and keep it at a constant temperature for 2-4 hours; D. After the isothermal treatment, the mixture is gradually cooled at a cooling rate of 1.0-2.5℃ / min. When the temperature drops to 95-100℃, a composite dispersion prepared by mixing silane coupling agent, amide nucleating agent, surfactant and water dispersion medium is added and stirred for 30-40 minutes. The mixture is then cooled to room temperature at a cooling rate of 1.0-2.5℃ / min, followed by solid-liquid separation and drying, or direct drying, to obtain modified bamboo powder fiber. E. Take 20-40 parts by weight of modified bamboo powder fiber and 60-80 parts by weight of polylactic acid or polybutylene succinate matrix resin, and then perform melt blending and injection molding.
2. The method for preparing highly crystalline bamboo powder fiber tableware according to claim 1, characterized in that, The bamboo powder in step A is natural bamboo powder that has been sieved through an 80-mesh screen.
3. The method for preparing highly crystalline bamboo powder fiber tableware according to claim 1, characterized in that, In step D, the composite dispersion is prepared by ultrasonic dispersion and has a solid content of 1.5-3.0 wt%; the amount of silane coupling agent added is 0.3-0.8 wt% of the mass of the blasted bamboo powder, and the amount of amide nucleating agent added is 1.0-2.0 wt% of the mass of the blasted bamboo powder; in step E, when the matrix resin is polylactic acid, the processing temperature is 155-180℃; when the matrix resin is polybutylene succinate, the processing temperature is 130-160℃.
4. The method for preparing highly crystalline bamboo powder fiber tableware according to claim 3, characterized in that, In the composite dispersion of step D, the amount of silane coupling agent added is 0.5-0.6 wt% of the mass of the blasted bamboo powder, and the amount of amide nucleating agent added is 1.2-1.6 wt% of the mass of the blasted bamboo powder.
5. The method for preparing highly crystalline bamboo powder fiber tableware according to claim 4, characterized in that, The silane coupling agent in step D is 3-aminopropyltriethoxysilane, and the amide nucleating agent is N,N'-ethylenebis-stearamide.
6. The method for preparing highly crystalline bamboo powder fiber tableware according to claim 1, characterized in that, In step D, the cooling rate to room temperature is 1.0 °C / min.
7. The method for preparing highly crystalline bamboo powder fiber tableware according to claim 1, characterized in that, The drying process in step D is either spray drying or freeze drying after filtration. When the drying process is spray drying, the inlet air temperature is 85-150℃ and the outlet air temperature is 42-90℃.
8. The method for preparing highly crystalline bamboo powder fiber tableware according to claim 1, characterized in that, In step E, the modified bamboo powder fiber has a mass fraction of 30 parts, and the matrix resin has a mass fraction of 70 parts.
9. The method for preparing highly crystalline bamboo powder fiber tableware according to claim 1, characterized in that, In step A, the liquid-solid mass ratio is 3:1-5:1 for impregnation, and the impregnation pretreatment temperature is 20-30℃ for 1-2 hours; in step B, the pressure is released in less than 0.1s; in step C, the solid content of the aqueous suspension is 10-20wt%, and the stirring rate is 100-300rpm.
Citation Information
Patent Citations
Bamboo powder filling biodegradable compound material and preparation method thereof
CN101942184A
Ultrafine bamboo powder modified biodegradable polyester and preparation method thereof
CN116515269A